2022
DOI: 10.15406/mojsm.2022.05.00113
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and kinetic variable determinants on vertical jump performance: a review

Abstract: The vertical jump is a task performed in various sports modalities and is considered a lower limb power test, that may provide information about the efficacy of several training programs. Although of the various types of jumps, two have been more used: the Squat Jump and the Countermovement Jump. Kinematics and kinetics variables are presented to describe the Squat Jump and Countermovement Jump, however, little is known about which variables are intrinsic in vertical jump performance. Thus, this review has two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Inter-muscular coordination, or the coordinated contraction of the muscles, refers to the way the muscles contract in a task-dependent order [40]. These findings support previous reports that have shown a positive correlation between peak power in a 40-kg conventional jump squat and CMJ height in Australian rules football players [41,42].…”
Section: Discussionsupporting
confidence: 87%
“…Inter-muscular coordination, or the coordinated contraction of the muscles, refers to the way the muscles contract in a task-dependent order [40]. These findings support previous reports that have shown a positive correlation between peak power in a 40-kg conventional jump squat and CMJ height in Australian rules football players [41,42].…”
Section: Discussionsupporting
confidence: 87%
“…The kinetic variables analyzed in this study are good indicators of jump performance, with some more influential than others. Moura and Okazaki (2022), identified that peak power can be the greatest indicator of muscle power during a jump, establishing a positive relationship with jump performance, whereas rate of force development may not predict alone a good jump performance, as it depends on type and velocity of contraction (Moura and Okazaki, 2022). In this present study, chicken wing block and swing block presented the higher values of peak power and max RFD than shuffle block.…”
Section: Discussionmentioning
confidence: 49%
“…A review article by Moura and Okazaki (2022) mentioned that the squat depth influences the jump height performance. The best jump performance happens when the knee flexion is smaller than 90 degrees, and when the squat reaches a greater depth, the lower the peak force.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations